Sr0.7Ce0.3MnO3-d as anode material for fuel-assisted solid oxide electrolysis cells - Yaremchenko, Aleksey (2022)
Long-term degradation remains the main issue for the viability of solid oxide electrolysis cell (SOEC) technology as a practical hydrogen production system. The principle of the so-called fuel-assisted electrolysis cell is to supply the low-grade fuel to the anode where it can react with oxygen, thus bringing down the oxygen chemical potential at the electrolyte/anode interface and improving its stability. The present work is aimed at the evaluation of Sr0.7Ce0.3MnO3-d perovskite for potential application as an anode in fuel-assisted SOEC. Sr0.7Ce0.3MnO3-d was synthesized by the glycine-nitrate technique with repeated calcinations at 900-1300°C to obtain phase-pure perovskite material. Ceramic samples were sintered in air at 1450°C. The oxide exhibits negligible variations of oxygen content under oxidizing conditions while reducing p(O2) below 10-4 atm at 750-900°C results in oxygen losses and reduction of Mn cations. The low-p(O2) stability boundary of the perovskite phase at 800°C corresponds to ~3×10-17 atm. Sr0.7Ce0.3MnO3-d shows good thermomechanical compatibility with solid electrolytes under oxidizing conditions; however, reduction at operation temperatures (800°C) leads to undesirable chemical expansion. The electrical conductivity of Sr0.7Ce0.3MnO3 ceramics is p-type electronic and decreases with reducing p(O2) but still exceeds 40 S/cm under anticipated oxygen electrode operation conditions. The electrochemical activity of Sr0.7Ce0.3MnO3 electrodes was evaluated in contact with YSZ solid electrolyte as a function of relevant parameters. The best performance was obtained for the cells with a CGO buffer layer and Sr0.7Ce0.3MnO3 electrodes infiltrated with PrOy (load of ~ 30 wt.%) that can show anodic overpotentials of ~50 mV under 400 mA/cm2 at 800°C in air.